1999
DOI: 10.1152/ajpheart.1999.276.4.h1207
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic contraction of small pulmonary arteries from normal and endotoxemic rats: fundamental role of NO

Abstract: The present study was aimed at examining the role of nitric oxide (NO) in the hypoxic contraction of isolated small pulmonary arteries (SPA) in the rat. Animals were treated with either saline (sham experiments) or Escherichia coli lipolysaccharide [LPS, to obtain expression of the inducible NO synthase (iNOS) in the lung] and killed 4 h later. SPA (300- to 600-μm outer diameter) were mounted as rings in organ chambers for the recording of isometric tension, precontracted with PGF2α, and exposed to either seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…These O 2 concentrations were shifted to higher values when the intensity of prestimulation was increased (1652) or when measurements were made in a rat strain more responsive to hypoxia (1691 656,799,814,900,903,935,991,1043,1045,1131,1151,1413,1430,1651,1652,1691,1896,1961,1976,2018,2089,2185). Moreover, substantial data suggested that the endothelium dependence of phase 1 was caused by an hypoxia-induced decrease in endothelial NO production, leading to smooth muscle contraction (506, 656,814,903,934,935,991,1151,1413,1430,1691,1896,1976,2018). In contrast, other studies reported that removal of endothelium did not eliminate or even enhanced phase 1 HPV (412, 413, 876,1038,1043,1151,1207,1208,1638,2190).…”
Section: Pulmonary Arteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…These O 2 concentrations were shifted to higher values when the intensity of prestimulation was increased (1652) or when measurements were made in a rat strain more responsive to hypoxia (1691 656,799,814,900,903,935,991,1043,1045,1131,1151,1413,1430,1651,1652,1691,1896,1961,1976,2018,2089,2185). Moreover, substantial data suggested that the endothelium dependence of phase 1 was caused by an hypoxia-induced decrease in endothelial NO production, leading to smooth muscle contraction (506, 656,814,903,934,935,991,1151,1413,1430,1691,1896,1976,2018). In contrast, other studies reported that removal of endothelium did not eliminate or even enhanced phase 1 HPV (412, 413, 876,1038,1043,1151,1207,1208,1638,2190).…”
Section: Pulmonary Arteriesmentioning
confidence: 99%
“…In rat (412), the magnitude of phase 2 HPV elicited by 6% O 2 was half of that elicited by 2% O 2 . With few exceptions (54, 139), phase 2 HPV was found to be endothelium-dependent (392,394,413,506,578,799,814,815,991,1038,1043,1044,1131,1639,1652,1896,2024). As discussed in section IVB2B, it is widely held that phase 2 HPV requires a diffusible contracting factor released by endothelium, which may act by increasing Ca 2ϩ sensitivity in pulmonary arterial smooth muscle.…”
Section: Pulmonary Arteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential down-regulation of HO-2 in these vascular tissues by NO would constantly reduce the production of CO, resulting in increased contractility and sensitivity to vasoconstrictors ). Under certain circumstances, such as severe hypoxia, NO production might be reduced due to a limited availability of O 2 as a substrate for NOS (Terraz et al, 1999). As a compensatory response of the vasculature during hypoxia, CO production from HO-2 would be increased to compensate for the shortage of NO.…”
Section: Interaction Of Heme Oxygenase/carbon Monoxide and Nitricmentioning
confidence: 99%
“…Numerous groups have demonstrated that inhibition of NO results in an increase of hypoxia-induced contraction [17][18][19][20] . But other investigators [21,22] have demonstrated that NO synthase (NOS) inhibitors reduce rather than potentiate HPV. Since the lung has a high capacity for the production of PGs, these attracted attention as potential mediators of HPV [23] .…”
Section: Introductionmentioning
confidence: 99%